Acetabular Labral Tears Are Common in Asymptomatic Contralateral Hips With Femoroacetabular Impingement. Issue 5 (May 2019) - Vahedi, Hamed; Aalirezaie, Arash; Azboy, Ibrahim; Daryoush, Tanine; Shahi, Alisina; Parvizi, Javad
Abstract: Background: The number of patients undergoing hip arthroscopy for labral tears has increased, but labral tears are sometimes seen in asymptomatic patients with femoroacetabular impingement (FAI). The frequency of this finding, however, has not been well characterized nor is the proportion of patients with previously asymptomatic labral tears who may later become symptomatic. Questions/purposes: The purpose of this study was to determine (1) the prevalence of labral tears and other intraarticular pathology in the asymptomatic contralateral hip of patients undergoing surgery for symptomatic FAI; (2) the likelihood that the asymptomatic hip had become symptomatic at latest followup; and (3) any association between MRI findings and age, sex, and body mass index (BMI) in both symptomatic and asymptomatic sides. Methods: This study included patients who were diagnosed with unilateral symptomatic FAI between 2013 and 2015 and who had an available MRI of both hips. The study included 100 patients (47 females, 53 males) with a mean age of 33 years (range, 17-57 years). Patients with a symptomatic contralateral hip (n = 56) or an unsuitable MRI for review based on both reviewers' consensus (n = 344) were excluded. The MRI of both hips was independently evaluated by two orthopaedic surgeons and interobserver reliability tested. The interobserver reliability for the two surgeons' MRI ratings was almost perfect (κ ≥ 0.85). The presence of a labral tear, an acetabular chondral lesion, subchondral acetabular cysts, and fibrocystic changes in the femoral head-neck junction was documented for both hips. At latest followup, asymptomatic hips were investigated for any symptomatic labral tears or surgical procedures resulting from FAI. Results: A labral tear was recorded in 97 (97%) and 96 (96%) of symptomatic hips, respectively, for each surgeon's evaluation. A labral tear was also detected in 41 (41%) and 43 (43%) of asymptomatic hips. In addition, an acetabular chondral lesion was detected in 32 (32%) and 35 (35%) of the symptomatic hips and 15 (15%) and 17 (17%) of the asymptomatic hips. At latest followup, nine of the patients were diagnosed with symptomatic labral tears in the contralateral asymptomatic hip and were treated. None of the radiologic parameters examined demonstrated an association with patient age, sex, or BMI in either symptomatic or asymptomatic hips. Conclusions: Labral tears and acetabular chondral lesions are common in the asymptomatic contralateral hip of patients undergoing surgery for FAI. The incidence of a symptomatic labral tear in these asymptomatic hips was 9% during 2 years of followup. We suggest that the decision to perform chondral or labral surgery in patients with FAI should be made with caution considering the relatively high prevalence of labral tears in asymptomatic hips and the low chance of development of symptoms. Level of Evidence: Level IV, case-series study.